2022
DOI: 10.3389/fendo.2022.810747
|View full text |Cite
|
Sign up to set email alerts
|

Partial Response After Toripalimab Plus Anlotinib for Advanced Metaplastic Breast Carcinoma: A Case Report

Abstract: Metaplastic breast carcinoma (MBC) is an aggressive subtype of breast cancer, accounting for <1%. The clinical outcome is unknown due to the lack of treatment options. Here, we present the case of a 58-year-old woman with advanced MBC, in which standard adjuvant chemotherapy was unsuccessful. In the second-line therapy, she received anti-angiogenic(anlotinib) therapy plus chemotherapy. Finally, she was subsequently treated with immunotherapy (toripalimab) combined anlotinib and achieved partial response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…This suggests a potential for enhanced effectiveness of immunotherapy-based treatments within this subgroup. Case reports have illustrated positive responses and clinical benefits with immunotherapy in patients diagnosed with BC-Mp ( 47 50 ). In the present study, one patient received pembrolizumab with chemotherapy within a clinical trial, achieving a PFS of 20 months (the longest in the cohort) and an OS of 21 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests a potential for enhanced effectiveness of immunotherapy-based treatments within this subgroup. Case reports have illustrated positive responses and clinical benefits with immunotherapy in patients diagnosed with BC-Mp ( 47 50 ). In the present study, one patient received pembrolizumab with chemotherapy within a clinical trial, achieving a PFS of 20 months (the longest in the cohort) and an OS of 21 months.…”
Section: Discussionmentioning
confidence: 99%
“…The trial specifically targets patients with HER2 − mBC-Mp with alterations in PIK3CA and PTEN. There are also a single report of successful applications of combined anti-angiogenic agent and immune check-point inhibitor ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, several case reports have demonstrated a remarkably durable response to IO with and without CT in the metastatic setting and pCR in the early setting [36][37][38][39][40] (Table 1). A case series published in 2021 showed that three out of five patients with metastatic MpBC responded to ICIs, of which one had mixed metaplastic squamous carcinoma with invasive lobular carcinoma and low ER expression, which achieved complete response [41].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a patient affected by advanced metaplastic BC not responsive to standard adjuvant chemotherapy partially responded to the immunotherapeutic TORIPALIMAB combined with the angiogenesis inhibitor ANLOTINIB [ 154 ].…”
Section: Effect Of Antiangiogenic Agents Combined With Immune Checkpo...mentioning
confidence: 99%